Non-linear Heart Rate Variability as a Discriminator of Internalizing Psychopathology and Negative Affect in Children With Internalizing Problems and Healthy Controls - Fiskum, Charlotte; Andersen, Tonje G.; Bornas, Xavier; Aslaksen, Per M.; Flaten, Magne A.; Jacobsen, Karl (Frontiers in Physiology, 2018)
Background Internalizing psychopathology and dysregulated negative aﬀect are characterized by dysregulation in the autonomic nervous system and reduced heart rate variability (HRV) due to increases in sympathetic activity alongside reduced vagal tone. The neurovisceral system is however a complex nonlinear system, and nonlinear indices related to psychopathology are so far less studied in children. Essential nonlinear properties of a system can be found in two main domains: the informational domain and the invariant domain. Sample entropy (SampEn) is a much-used method from the informational domain, while detrended fluctuation analysis (DFA) represents a widely-used method from the invariant domain. To see if nonlinear HRV can provide information beyond linear indices of autonomic activation, this study investigated SampEn and DFA as discriminators of internalizing psychopathology and negative aﬀect alongside measures of vagally-mediated HRV and sympathetic activation. Material and Methods 32 children with internalizing diﬃculties and 25 healthy controls (aged 9-13) were assessed with the Child Behavior Checklist and the Early Adolescent Temperament Questionnaire, Revised, giving an estimate of internalizing psychopathology, negative aﬀect and eﬀortful control, a protective factor against psychopathology. Five minute electrocardiogram and impedance cardiography recordings were collected during a resting baseline, giving estimates of SampEn, DFA short-term scaling exponent α1 , root mean square of successive diﬀerences (RMSSD) and pre-ejection period (PEP). Between-group diﬀerences and correlations were assessed with parametric and non-parametric tests, and the relationships between cardiac variables, psychopathology and negative aﬀect were assessed using generalized linear modeling. Results and Conclusions SampEn and DFA were not significantly diﬀerent between the groups. SampEn was weakly negatively related to heart rate (HR) in the controls, while DFA was moderately negatively related to RMSSD in both groups, and moderately positively related to HR in the clinical sample. SampEn was significantly associated with internalizing psychopathology and negative aﬀect. DFA was significantly related to internalizing psychopathology. Conclusions Higher invariant self-similarity was linked to less psychopathology. Higher informational entropy was related to less psychopathology and less negative aﬀect, and may provide an index of the organizational flexibility of the neurovisceral system.